Poisoning by (Conium maculatum) and liver deficiency in a bovine. Clinical case - Cueva Rodríguez, Medali (2025)
In the majority of cases, poisonings in livestock occur accidentally. The primary causes of poisoning are associated with the ingestion of toxic plants, which contain a range of substances including alkaloids, nitrates, saponins, and others, that can lead to fatal outcomes. The objective of the investigation was to ascertain the cause of death of the bovine. The animal in question was a Simmental breed heifer, aged one year and two months, weighing 250 kg live, and displaying symptoms consistent with Conium maculatum poisoning. The results of the autopsy demonstrated the following: the external examination revealed slight profuse hemorrhage and icteric mucosa on the lips, a pale and icteric flaking muzzle, pale and icteric vulvar and ocular mucosa, and small hemorrhagic vesicles focused at the level of the cross, hip, and dewlap. Additionally, the abdomen was found to be slightly enlarged with a dull sound. The internal examination revealed the presence of generalized jaundice, icteric pleural tissue, icteric myocardium, cardiomegaly with flaccidity in the left ventricle, and icteric peritoneum in the abdomen. Additionally, the rumen and intestines exhibited apparently normal contents. The abomasum and liver exhibited adhesions with necrotic tissue, hepatomegaly, necrotic tissue at the level of the common bile duct, rupture of the gallbladder with the content distributed throughout the bile ducts, and an abundant blackish liquid with a putrid odor. Laboratory tests to rule out bluetongue and bovine vesicular stomatitis were conducted at the National Agrarian Health System (SENASA) and yielded negative results for both diseases. It was determined that the bovine had died as a result of poisoning by hemlock and liver deficiency.